Economic and social benefits related to the promotion of dairy and beef cattle welfare - da Costa, Mateus Paranhos [UNESP]; Ceballos, Maria Camila (My University, 2021)
This article aims to contribute with information on how to minimize stress during dairy and beef cattle handling and analyze situations in which animal welfare problems compromise human well-being and the production system’s economy. This analysis considers the five domains of animal welfare (nutrition, health, environment, behavior, and mental states), which evaluate animal welfare in an integrative way. We present practical examples of how the adoption of good animal welfare handling practices contributes to better working conditions for people and improves their quality of life. There are also economic benefits for producers, providing an opportunity to implement a new strategy for promoting sustainable livestock production, applying the concept of “a life worth living” for animals and human beings living or working on farms.
Benefícios econômicos e sociais relacionados à promoção do bem-estar de bovinos leiteiros e de corte
Keywords: Behavior; Environment; Handling; Health; Sustainability